Visible light response photocatalytic carbon mineralized cement-based coating and preparation method thereof
By combining inorganic cementitious materials with visible light-responsive polymer carbon nitride photocatalysts, a porous structure of photocatalytic carbon mineralized cement-based coating is formed, which solves the problems of low catalytic efficiency, poor bonding performance and insufficient durability in the prior art, and achieves the effect of efficient purification of NOX and organic pollutants under visible light.
Patent Information
- Application Number
- CN202510602046.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-12
- Publication Date
- 2025-07-18
AI Technical Summary
The existing photocatalytic coatings have low catalytic efficiency under visible light conditions, poor bonding performance, insufficient durability, and difficult to effectively purify NOX and organic pollutants in places with limited light conditions.
Inorganic cementitious materials are combined with visible light-responsive polymer carbon nitride photocatalyst, supplemented with carbonate-based carbonizing agents, and spraying and conducting in-situ carbon mineralization reactions to form a photocatalytic carbon mineralized cement-based coating with a porous structure.
Effectively purify NOX and organic pollutants under visible light, with good bonding performance and durability, and is suitable for self-cleaning of building surfaces and air purification.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of building materials, and particularly to a visible light-responsive photocatalytic carbonated cement-based coating and a preparation method thereof. Background Art
[0002] With the rapid development of industry, a large amount of fossil fuels are burned, resulting in the emission of carbon dioxide gas, which causes global warming, such as the rise of sea level, poor growth of plants, and damage to the ecosystem. Therefore, carbonated cement has emerged. The inorganic cementitious material used in this cement can undergo a carbonation reaction with carbon dioxide, which can not only make itself reach a certain strength but also solidify carbon dioxide in the reaction products, thus attracting extensive attention.
[0003] The emission of automobile exhaust (the main component is nitrogen oxides (NO X )) not only damages the ecological environment but also harms human health. For example, the concentration of NO X is relatively high in semi-closed structures (such as tunnels and underground garages), which will affect human health; organic pollutants not only affect the water environment but also human health, such as congo red, 4-nitrophenol, methylene blue, etc. In the face of these problems, using clean energy to improve the environmental crisis is the only choice. Among them, photocatalytic technology, as a green and sustainable environmental remediation technology, shows good prospects in the field of environmental pollution control. Photocatalytic technology mainly uses the redox ability of photocatalysts under light irradiation to remove NO X and organic pollutants, so as to achieve the effect of purifying exhaust gas. Therefore, it has attracted extensive attention at home and abroad.
[0004] At present, the most commonly used photocatalyst is TiO2, which has the advantages of stable chemical properties and stable catalytic activity, and is widely used in self-cleaning and exhaust gas purification. The "Negative Carbon Self-Cleaning Inorganic Coating, Its Preparation Method and Obtained Coating" with patent number CN115058132B and the "TiO2 Coating with Photocatalytic Function and Preparation Method" with patent number CN111203218A both mention relevant coatings with photocatalytic functions, which have high catalytic activity under ultraviolet light. However, these coating materials use TiO2 as the photocatalytic material and need to be irradiated by ultraviolet light for a long time to achieve the effects of self-cleaning and air purification. Ultraviolet light only accounts for 5% of the spectrum, greatly limiting its scope of application. Especially in scenarios such as tunnels and underground garages where the lighting conditions are limited and the intensity of ultraviolet light is not high, the application of these TiO2 photocatalytic coatings is restricted. The "Preparation Method of a Photocatalytic Cementitious Material" with patent number CN115180976A prepares a photocatalytic cementitious material, mainly using a coupling agent as the bonding layer and fixing polymer carbon nitride on it to achieve the photocatalytic effect. The "Photocatalytic Carbon Nitride Coating for Visible Light Response on the Surface of Building Materials and Its Preparation Method" with patent number CN111978762A prepares a photocatalytic carbon nitride coating for visible light response on the surface of building materials and its preparation method, mainly using an organic binder (polyurethane polymer) and an inorganic binder (sodium silicate) as the bonding layer to fix polymer carbon nitride, thereby achieving the photocatalytic effect. Although the binders used in these two patents have good bonding properties, they will affect the photocatalytic effect and have poor weather resistance. The "Photocatalytic Cementitious Material Loaded with Carbon Nitride and Its Preparation Method" with patent number CN114904553A prepares a photocatalytic cementitious material loaded with carbon nitride, preparing a suspension of calcium hydroxide and polymer carbon nitride and spraying it on the surface of the cementitious material. After curing, it plays a role in fixing polymer carbon nitride. Although this patent has good photocatalytic performance in loading the photocatalytic material on the cementitious surface, it has the problem of poor bonding performance.
[0005] With the increasing requirements for energy conservation and emission reduction in the construction industry, it is necessary to develop a photocatalytic coating with the characteristics of environmental friendliness, high photocatalytic efficiency, good durability, etc. Summary of the Invention
[0006] The purpose of the present invention is to overcome the above technical deficiencies and propose a visible light-responsive photocatalytic carbonated cementitious coating and its preparation method.
[0007] In the first aspect of the present invention, a visible light-responsive photocatalytic carbonated cementitious coating is provided, including the following materials:
[0008] Inorganic cementitious materials, photocatalysts, auxiliary carbonizing agents, and water, where the amounts are set by weight as follows: 91 to 99 parts of inorganic cementitious materials, 1 to 9 parts of photocatalysts, 1 to 10 parts of auxiliary carbonizing agents, and 80 to 110 parts of water;
[0009] The inorganic cementitious materials are carbonized mineral components or industrial solid wastes containing at least 60% carbonization active components, and the carbonization active components are one or more combinations of dicalcium silicate, wollastonite, and rankinite:
[0010] The photocatalyst includes visible-light-responsive polymeric carbon nitride;
[0011] The auxiliary carbonizing agent is one or more of sodium bicarbonate, sodium carbonate, nano-calcium carbonate, ammonium carbonate, and ammonium bicarbonate.
[0012] Preferably, the dicalcium silicate is γ-dicalcium silicate and β-dicalcium silicate.
[0013] Preferably, the preparation method of the visible-light-responsive polymeric carbon nitride is as follows: Weigh 4 g of melamine and 20 g of ammonium chloride and mix them. The mixed powder is ground in a mortar, then the ground powder is loaded into a crucible and placed in a muffle furnace together. The temperature of the muffle furnace is set at 550 °C, the heating rate is 5 °C / min, and it is kept warm for 4 h. After natural cooling, the required visible-light-responsive polymeric carbon nitride is obtained.
[0014] Preferably, the mass ratio of the sum of the masses of the inorganic cementitious materials and the photocatalyst to the mass of water is 1:(0.8 to 1.1).
[0015] Preferably, the mass ratio of the sum of the masses of the inorganic cementitious materials and the photocatalyst to the mass of the photocatalyst is 1:(0.01 to 0.09).
[0016] Preferably, the mass ratio of the sum of the masses of the inorganic cementitious materials and the photocatalyst to the mass of the auxiliary carbonizing agent is 1:(0.01 to 1.0).
[0017] Preferably, the colors of the selected dicalcium silicate, wollastonite, and rankinite all belong to white or off-white, and the fineness is less than 0.075 mm.
[0018] Preferably, the visible-light-responsive photocatalytic carbonated cementitious coating is obtained by coating on the surface of a substrate and undergoing an in-situ carbonation reaction.
[0019] Preferably, the visible-light-responsive photocatalytic carbonated cementitious coating is coated on the surface of the substrate by spraying, and a gas with a CO2 mass concentration of 20 to 100% is used as the spraying gas source during the spraying process.
[0020] Preferably, any one or several inorganic cementitious materials selected from the range all have good carbonation activity.
[0021] In a second aspect of the present invention, there is provided a method for fabricating a substrate, including coating the surface of the substrate with the above-mentioned visible-light-responsive photocatalytic carbonated cementitious coating.
[0022] In a third aspect of the present invention, there is provided a method for preparing a visible-light-responsive photocatalytic carbonated cementitious coating, including the following steps:
[0023] First, mix the photocatalyst with water, then place it in an ultrasonic machine and ultrasonicate for a certain time to obtain a photocatalyst suspension. Then, add the inorganic cementitious material and the auxiliary carbonating agent to the photocatalyst suspension, mix the materials and stir, and finally spray them on the surface of the substrate for in-situ carbonation reaction to obtain a visible-light-responsive photocatalytic carbonated cementitious coating.
[0024] Preferably, the set time for ultrasonication is 30 min.
[0025] Compared with the prior art, the beneficial effects of the present invention include:
[0026] By incorporating a photocatalyst with visible-light-responsive function, the present invention can achieve the effect of purifying and removing pollutants under visible light irradiation;
[0027] The present invention uses an inorganic cementitious material with carbonation activity to generate calcium carbonate and silica gel in a carbon dioxide environment, which can achieve the effect of carbon sequestration while meeting the requirements of mechanical properties, bonding properties, and durability;
[0028] By regulating the ratio of the photocatalyst and the inorganic cementitious material, the photocatalyst is partially wrapped in calcium carbonate crystals or adsorbed on the surface of calcium carbonate, having good anti-scouring performance;
[0029] Through the action of the visible-light-responsive photocatalyst, the present invention converts NO X into soluble nitrate, which has the characteristics of being easy to clean, effectively avoiding the accumulation of nitric acid on the surface of polymeric carbon nitride, thereby improving the durability of the photocatalyst; all raw materials used in the present invention are inorganic materials. The visible-light-responsive photocatalytic carbonated cementitious coating prepared therefrom not only has a visible-light-responsive photocatalytic function, but also has good bonding properties and durability. It is an environmentally friendly carbonated coating that can be widely applied to the surface of buildings to play the role of self-cleaning and air purification. Specific embodiments
[0030] The present invention will be described in detail below with different manufacturing processes. The listed embodiments can enable those skilled in the art to better understand the present invention, but do not limit the present invention in any form. For example, the present invention can be extended and applied to other fields.
[0031] The first aspect of the present invention provides a visible-light-responsive photocatalytic carbonated cement-based coating. By weight, its raw materials include: 91-99 parts of inorganic cementitious materials, 1-9 parts of photocatalyst, 1-10 parts of auxiliary carbonating agent, and 80-110 parts of water.
[0032] In the present invention, the above-mentioned inorganic cementitious materials have carbonation activity. During the carbonation process, a certain amount of CO2 needs to be absorbed to enable the coating to have a certain strength and provide a stable chemical environment for the photocatalyst without affecting the photocatalytic activity of the photocatalyst, so that it has a good self-cleaning effect. The above-mentioned inorganic cementitious materials can directly be carbonation-active components such as dicalcium silicate (β and γ), wollastonite, and rankinite. The present invention does not limit this.
[0033] In some specific embodiments of the present invention, the particle size of the above-mentioned inorganic cementitious materials is less than 75 μm.
[0034] In the present invention, the mass ratio of the sum of the masses of the inorganic cementitious materials and the photocatalyst to the mass of water is 1:(0.8-1.1). In multiple experiments, it was found that the data is more preferably 1:(0.8-1.1). And the following rule was found: The mass ratio of the inorganic cementitious materials to water has a great influence on the coating performance. As the mass ratio of the inorganic cementitious materials to water decreases, the coating surface cannot be evenly laid.
[0035] In the present invention, on the one hand, the above-mentioned photocatalyst has a good photocatalytic self-cleaning effect. For example, in some specific embodiments of the present invention, the removal rate of NO by 3 g of the photocatalyst can reach 33.4%. On the other hand, it can stably combine with the inorganic cementitious materials. Further, the photocatalyst is polymeric carbon nitride.
[0036] In the present invention, the above-mentioned photocatalyst accounts for 10%-90% of the total mass of the inorganic cementitious materials and the photocatalyst, including but not limited to 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, etc. The present invention does not limit this, and those skilled in the art can select according to the actual situation. And the following rule was found: As the amount of the photocatalyst increases, the photocatalytic effect first increases and then basically remains unchanged. A small amount of the photocatalytic material can improve the mechanical properties, and excessive incorporation will reduce the mechanical properties of the coating.
[0037] In some preferred embodiments of the present invention, the mass ratio of the sum of the masses of the inorganic cementitious material and the photocatalyst to the mass of the photocatalyst is 1:(0.01 - 0.09). During the specific test process, it was found that: under the condition of the same mass ratio of the inorganic cementitious material to water, with the increase of the photocatalyst, both the photocatalytic effect and the mechanical properties showed a trend of first increasing and then decreasing. When the mass ratio of the inorganic cementitious material to the photocatalyst is 1:(0.01 - 0.09), the formed coating has the optimal performance.
[0038] In the present invention, the above-mentioned auxiliary carbonating agent is a carbonate or bicarbonate. Specifically, the above-mentioned auxiliary carbonating agent can be one or more of sodium bicarbonate, sodium carbonate, nano-calcium carbonate, ammonium carbonate, and ammonium bicarbonate. In the present invention, adding the auxiliary carbonating agent can improve the coating hardness and the photocatalytic effect. Further, the mass ratio of the sum of the masses of the inorganic cementitious material and the photocatalyst to the mass of the auxiliary carbonating agent is 1:(0.4 - 0.8).
[0039] In some specific embodiments of the present invention, the above-mentioned visible-light-responsive photocatalytic carbonated cement-based coating, by weight, comprises: 91 - 99 parts of inorganic cementitious material, 1 - 7 parts of photocatalyst, 1 - 10 parts of auxiliary carbonating agent, and 80 - 110 parts of water.
[0040] The second aspect of the present invention provides a method for preparing a visible-light-responsive photocatalytic carbonated cement-based coating, comprising the following steps:
[0041] First, mix the photocatalyst with water, put it into an ultrasonic machine and ultrasonic for 30 min to obtain a photocatalyst suspension, then add the inorganic cementitious material and the auxiliary carbonating agent to the photocatalyst suspension, and stir for 5 min. Finally, spray it on the surface of the substrate to carry out in-situ carbonation reaction to obtain a visible-light-responsive photocatalytic self-cleaning inorganic coating (i.e., a visible-light-responsive photocatalytic carbonated cement-based coating).
[0042] In the present invention, the above-mentioned visible-light-responsive photocatalytic carbonated cement-based coating can be coated on the surface of the substrate by spraying, brushing and other methods, and the formed coating has good weather resistance. In some specific embodiments of the present invention, the coating thickness is 0.5 - 0.7 mm.
[0043] In some preferred embodiments of the present invention, the above-mentioned visible-light-responsive photocatalytic coating is applied to the surface of the substrate by spraying, and a gas containing CO2 is used as the spraying gas source during the spraying process to achieve in-situ carbon mineralization. By using a certain concentration of CO2 gas as the spraying gas source, the present invention realizes in-situ carbon mineralization, making the formed coating have a certain hardness and a porous structure. The preferable concentration obtained in the experiment is: the mass concentration of carbon dioxide gas is 20-99.9%, including but not limited to 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 99.9%, etc. It should be noted here that the carbon dioxide mass concentration mentioned in this solution is 20-100% of CO2 gas as the spraying gas source. Since the purity of the gas cannot reach 100%, the actually obtained concentration of 99.9% represents the meaning of 100%.
[0044] The present invention places no restrictions on the type of the above-mentioned substrate. For example, it can be a cement-based material. To avoid repetition, in the following embodiments of the present invention, some raw materials are summarized as follows:
[0045] Example 1
[0046] By weight, the visible-light-responsive photocatalytic carbonated cement-based coating of this example is composed of: 99 parts of dicalcium silicate, 1 part of photocatalyst, 4 parts of sodium bicarbonate, and 80 parts of water.
[0047] Using a CO2 gas with a mass concentration of 99.9% as the spraying gas source, the above-mentioned visible-light-responsive photocatalytic coating is applied on the surface of the cement matrix and forms a self-cleaning inorganic coating on the surface of the cement matrix through an in-situ carbon mineralization process.
[0048] Example 2
[0049] By weight, the visible-light-responsive photocatalytic carbonated cement-based coating of this example is composed of: 99 parts of dicalcium silicate, 1 part of photocatalyst, 4 parts of sodium bicarbonate, and 85 parts of water.
[0050] Using a CO2 gas with a mass concentration of 80% as the spraying gas source, the above-mentioned visible-light-responsive photocatalytic coating is applied on the surface of the cement matrix and forms a self-cleaning inorganic coating on the surface of the cement matrix through an in-situ carbon mineralization process.
[0051] Example 3
[0052] By weight, the visible-light-responsive photocatalytic carbonated cement-based coating of this example is composed of: 97 parts of dicalcium silicate, 3 parts of photocatalyst, 5 parts of sodium bicarbonate, and 90 parts of water.
[0053] Using CO2 gas with a mass concentration of 99.9% as the spraying gas source, the above-mentioned visible-light-responsive catalytic coating is applied on the surface of the cement matrix, and through an in-situ carbonation process, a visible-light-responsive photocatalytic carbonated cement-based coating is formed on the surface of the cement matrix.
[0054] Example 4
[0055] By weight, the composition of the visible-light-responsive photocatalytic carbonated cement-based coating in this example is: 95 parts of dicalcium silicate, 5 parts of photocatalyst, 6 parts of sodium bicarbonate, and 95 parts of water.
[0056] Using CO2 gas with a mass concentration of 99.9% as the spraying gas source, the above-mentioned visible-light-responsive photocatalytic coating is applied on the surface of the cement matrix, and through an in-situ carbonation process, a visible-light-responsive photocatalytic carbonated cement-based coating is formed on the surface of the cement matrix.
[0057] Example 5
[0058] By weight, the composition of the visible-light-responsive photocatalytic carbonated cement-based coating in this example is: 93 parts of dicalcium silicate, 7 parts of photocatalyst, 7 parts of sodium bicarbonate, and 100 parts of water.
[0059] The coating preparation process is the same as that in Example 1.
[0060] Example 6
[0061] By weight, the composition of the visible-light-responsive photocatalytic carbonated cement-based coating in this example is: 91 parts of dicalcium silicate, 9 parts of photocatalyst, 8 parts of sodium bicarbonate, and 105 parts of water.
[0062] The coating preparation process is the same as that in Example 1.
[0063] Example 7
[0064] By weight, the composition of the visible-light-responsive photocatalytic carbonated cement-based coating in this example is: 95 parts of dicalcium silicate, 5 parts of photocatalyst, 10 parts of sodium bicarbonate, and 110 parts of water.
[0065] Using CO2 gas with a mass concentration of 99.9% as the spraying gas source, the above-mentioned visible-light-responsive photocatalytic coating is applied on the surface of the cement matrix, and through an in-situ carbonation process, a self-cleaning inorganic coating is formed on the surface of the cement matrix.
[0066] Example 8
[0067] By weight, the composition of the visible-light-responsive photocatalytic carbonated cement-based coating in this example is: 95 parts of dicalcium silicate, 5 parts of photocatalyst, 10 parts of sodium bicarbonate, and 110 parts of water.
[0068] Use CO2 gas with a mass concentration of 20% as the spraying gas source, and form a self-cleaning inorganic coating on the surface of the cement matrix by applying the above visible light-responsive photocatalytic coating on the cement matrix surface and through an in-situ carbon mineralization process.
[0069] Comparative Example 1 (without adding polymeric carbon nitride)
[0070] By weight, the visible light-responsive photocatalytic carbonated cement-based coating of this comparative example is composed of: 99 parts of dicalcium silicate, 0 parts of photocatalyst, 4 parts of sodium bicarbonate, and 85 parts of water.
[0071] The coating preparation process is the same as that in Example 1.
[0072] Comparative Example 2 (without adding auxiliary carbonizing agent)
[0073] By weight, the visible light-responsive photocatalytic carbonated cement-based coating of this comparative example is composed of: 99 parts of dicalcium silicate, 1 part of photocatalyst, 0 parts of sodium bicarbonate, and 85 parts of water.
[0074] The coating preparation process is the same as that in Example 1.
[0075] Comparative Example 3 (without adding polymeric carbon nitride)
[0076] By weight, the visible light-responsive photocatalytic carbonated cement-based coating of this comparative example is composed of: 99 parts of dicalcium silicate, 0 parts of photocatalyst, 4 parts of sodium bicarbonate, and 85 parts of water.
[0077] The coating preparation process is the same as that in Example 2.
[0078] Comparative Example 4 (without adding auxiliary carbonizing agent)
[0079] By weight, the visible light-responsive photocatalytic carbonated cement-based coating of this comparative example is composed of: 99 parts of dicalcium silicate, 1 part of photocatalyst, 0 parts of sodium bicarbonate, and 85 parts of water.
[0080] The coating preparation process is the same as that in Example 2.
[0081] Conduct coating bond strength tests, NO X degradation tests, Rhodamine B self-cleaning tests, and erosion durability tests on the above-obtained different coatings. The main test conditions are as follows:
[0082] 1. Bond strength test: Use a tensile tester to detect the bond strength of the coating. Fix the coating and a circular pull ring with epoxy resin and conduct multiple pull-outs; use a loading rate of 0.08 mm / min until the interface is damaged, and finally take the average value of the results.
[0083] 2. NO xTest: Place the sample to be tested in a standard reactor (ISO / DIS 22197–1). By adjusting the distance between the light source of a 300W xenon lamp and the reactor, the light intensity on the sample surface is made 100 mW / cm 2 −1. By adjusting the flow rates of dry air, wet air, and NO gas, the total flow rate of the mixed gas is made 0.6 L·min - −1, the relative humidity is 50 ± 2%, and the NO gas concentration is 1000 ppm ± 50 ppb. The analysis system consists of a NO x analyzer and a computer for data acquisition. After passing through the reactor, the target gas directly enters the NO x analyzer. The NO x analyzer monitors the concentrations of NO and NO2 in the target gas in real time through the principle of photoluminescence.
[0084] 3. Self-cleaning test of rhodamine B: Uniformly drop 1 ml of rhodamine B solution (1 mmol / L) onto the surface of a cylindrical sample (20 mm in diameter and 20 mm in height). Place the sample under a 300W xenon lamp. The light passes through an ultraviolet cut-off filter (λ ≥ 420 nm), and the light intensity on the sample surface is controlled to be 100 mW / cm 2 −1. After 1 h of illumination, evaluate the efficiency of the sample in degrading rhodamine B by comparing the color change on the sample surface.
[0085] 4. Rainwater scouring durability test: Place the visible light-responsive photocatalytic coating material under a water flow with a flow rate of 600 ml / min for 1 day, and then test the ability to degrade NO x .
[0086] Table 1 Experimental results of Examples 1 to 6 and Comparative Examples 1 to 4 above
[0087]
[0088]
[0089] It can be seen from Table 1 that, compared with the comparative examples, the coatings formed in each embodiment of the present invention all have good self-cleaning effects, mechanical properties, and durability.
[0090] The specific embodiments of the present invention described above do not constitute a limitation to the protection scope of the present invention. Any other corresponding changes and deformations made according to the technical concept of the present invention should be included within the protection scope of the claims of the present invention.
Claims
1. A visible-light-responsive photocatalytic carbon mineralized cement-based coating, characterized in that: It includes the following materials: Inorganic cementitious materials, photocatalysts, auxiliary carbonizing agents and water, and are set according to parts by weight as follows: 91-99 parts of inorganic cementitious materials, 1-9 parts of photocatalysts, 1-10 parts of auxiliary carbonizing agents and 80-110 parts of water; The inorganic cementitious materials are carbonized mineral components or industrial solid wastes containing at least 60% of carbonization active components, and the carbonization active components are one or a combination of dicalcium silicate, wollastonite and rankinite; The photocatalyst includes polymer carbon nitride responsive to visible light; The auxiliary carbonizing agent is one or more of sodium bicarbonate, sodium carbonate, nano calcium carbonate, ammonium carbonate and ammonium bicarbonate.
2. The visible light-responsive photocatalytic carbonated cementitious coating according to claim 1, characterized in that: The dicalcium silicate is γ-dicalcium silicate and β-dicalcium silicate.
3. The visible light-responsive photocatalytic carbonated cementitious coating according to claim 1, characterized in that: The preparation method of the visible light-responsive polymer carbon nitride is as follows: Weigh 4 g of melamine and 20 g of ammonium chloride and mix them. The mixed powder is ground by a mortar, and then the ground powder is loaded into a crucible and placed in a muffle furnace together. The temperature of the muffle furnace is set at 550 °C, the heating rate is 5 °C / min, keep warm for 4 h, and after natural cooling, the required visible light-responsive polymer carbon nitride is obtained.
4. The visible light-responsive photocatalytic carbonated cementitious coating according to claim 1, characterized in that: The mass ratio of the sum of the masses of the inorganic cementitious materials and the photocatalyst to the mass of water is 1:(0.8-1.1).
5. The visible light-responsive photocatalytic carbonated cementitious coating according to claim 1, characterized in that: The mass ratio of the sum of the masses of the inorganic cementitious materials and the photocatalyst to the mass of the photocatalyst is 1:(0.01-0.09).
6. The visible light-responsive photocatalytic carbonated cementitious coating according to claim 1, characterized in that: The mass ratio of the sum of the masses of the inorganic cementitious materials and the photocatalyst to the mass of the auxiliary carbonizing agent is 1:(0.01-1.0).
7. The visible light-responsive photocatalytic carbonated cementitious coating according to claim 1, characterized in that: The selected dicalcium silicate, wollastonite and rankinite are all white or off-white in color and have a fineness of less than 0.075 mm.
8. The visible light-responsive photocatalytic carbon mineralized cement-based coating according to any one of claims 1 to 7, characterized in that: The visible light-responsive photocatalytic carbonated cementitious coating is obtained by coating on the surface of a substrate and undergoing an in-situ carbonation reaction.
9. The visible light-responsive photocatalytic carbonated cement-based coating according to claim 8, characterized in that: The visible light-responsive photocatalytic carbonated cementitious coating is coated on the surface of the substrate by spraying, and a gas with a CO2 mass concentration of 20-100% is used as the spraying gas source during the spraying process.
10. The preparation method of the visible light-responsive photocatalytic carbon mineralized cement-based coating according to claim 9, characterized in that It includes the following steps: First, mix the photocatalyst with water, put it into an ultrasonic machine and ultrasonic for a certain time to obtain a photocatalyst suspension, then add the inorganic cementitious materials and the auxiliary carbonizing agent to the photocatalyst suspension, mix the materials and stir, and finally spray them on the surface of the substrate to carry out an in-situ carbonization reaction to obtain the visible light-responsive photocatalytic carbonated cementitious coating.
Citation Information
Patent Citations
TiO2 coating with photocatalysis function and preparation method
CN111203218A
Carbon nitride photocatalytic coating suitable for visible light response on surface of building material and preparation method of carbon nitride photocatalytic coating
CN111978762A
Carbon nitride-loaded photocatalytic cement-based material and preparation method thereof
CN114904553A
A negative carbon self-cleaning inorganic coating, its preparation method and the obtained coating
CN115058132B
Preparation method of photocatalytic cement-based material
CN115180976A